Delayed Reverse Sural Artery Flap with Skin Pedicle Technique Versus Standard Island Sural Artery Flap for Reconstruction of Lower Leg, Ankle and Malleoli - Naeem, Abdullah Y.; Al-Bahlooli, Saeed H.; Almalahy, Ahmed; Abdulmughny, Yasser; Aitha, Taher (Thamar University Journal of Natural & Applied Sciences, 2023)
Background and objectives: Standard reverse island sural artery flap is the most common usage for distal third defects of the leg. However many authors reported 36 % complication rate mainly partial or complete flap loss , that is attributed to venous congestion. Delayed reverse sural artery flap in two stages with skin pedicle technique is reliable and less complicated. In this study was compare between the results of both techniques.Patients & Methods: The study included forty patients presented to AL-Wahda University Hospital and 48 Military Hospital , after trauma of lower leg with complete loss of soft tissue and exposure of underlying structures ,within periods Oct 2013 to May 2017. The patients were thirty male and ten female , their age ranged between fifteen to sixty years old . Reverse island sural artery flap was used in twenty patients, while delayed sural artery flap was used in twenty patients too.The results of both techniques were compared.Results: In our study the standard reverse island sural artery flap is good option for reconstruction of lower leg , ankle and malleoli defect ,which is performed in twenty patients , the partial necrosis occur in 20% patients and three cases with flap failure ,the venous congestion occur in 35% of patients In this study, we performed reconstruction of the lower leg, heel , and malleoli in another twenty patients by delayed reverse sural artery flap with skin pedicle technique, the flap necrosis occur only in one case and partial flap necrosis occur in two cases only, in comparison with standard technique of reverse island sural artery flap, the venous congestion occur only in four patients 20% , two cases recovering the congestion by leg elevation and improving the patients hydration , and two cases of venous congestion progressive to partial flap necrosis. Partial necrosis occur in two cases, complete flap necrosis occur in one case and 95% of patients satisfaction in discharge.Conclusion: The delayed reverse sural artery flap with skin pedicle is very important to avoid of venous congestion and flap failure , especially in old patients , DM , and in patients with peripheral vascular diseases. The goal of our study were achieved , and the patients improved functionally and attained their routine activity. By this technique and modification, make the delayed sural artery flap the first choice in reconstruction of the lower third defect of leg , heel and ankle. and is less postoperative venous congestion and flap failure. Delayed sural artery flap in two stages with skin pedicle technique is convenience and less complication particularly for old patients with diabetes mellitus and peripheral limb ischemia or venous insufficiency.